Предмет: Математика,
автор: yakov4uksofija
Спростити та обчислити вираз -18(0,6х-16)+8(2,6х-4) якщо х=-0,1
Ответы
Автор ответа:
0
Ответ:284,52
Пошаговое объяснение:
-18(0,6х-16)+8(2,6х-4)=
-18×(0,6×(-0,1)-16)+8×(2,6×(-0,1)-4)=
-18×(-0,06-16)+8×(-0,26-4)=
-18×(-15,94)+8×(-0,3)=
286,92+(-2,4)=
284,52
Похожие вопросы
Предмет: Английский язык,
автор: помогите662
Предмет: Українська література,
автор: anya2814
Предмет: Английский язык,
автор: RonaldMCdanald
Предмет: Алгебра,
автор: 27Ekaterina09
Предмет: Алгебра,
автор: maximverhovih2